2015
DOI: 10.3945/ajcn.114.098590
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pure flavonoids epicatechin and quercetin on vascular function and cardiometabolic health: a randomized, double-blind, placebo-controlled, crossover trial

Abstract: Our results suggest that epicatechin may in part contribute to the cardioprotective effects of cocoa and tea by improving insulin resistance. It is unlikely that quercetin plays an important role in the cardioprotective effects of tea. This study was registered at clinicaltrials.gov as NCT01691404.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(231 citation statements)
references
References 52 publications
8
207
0
2
Order By: Relevance
“…It works through counteracting the actions of contracting factors, including angiotensin-11 and endothelin-1. Various studies have isolated specific components of GT and observed an augmentation of NO status (Loke et al 2008). Similarly, oral administration of catechins increased NO levels and also decreased enodthelin-1 concentrations (a vasoconstrictor) (Persson et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…It works through counteracting the actions of contracting factors, including angiotensin-11 and endothelin-1. Various studies have isolated specific components of GT and observed an augmentation of NO status (Loke et al 2008). Similarly, oral administration of catechins increased NO levels and also decreased enodthelin-1 concentrations (a vasoconstrictor) (Persson et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Quercetin has been demonstrated to be equally or more effective than resveratrol in attenuating the TNF levels [221]. The safety, tolerability and efficacy of resveratrol, genistein, sylimarin and quercetin has also been proven in multiple randomized, double-blind, placebo controlled clinical studies [218][219][220][222][223][224][225][226]. In addition, many flavonoids have also been reported to possess antibacterial, antifungal and antiviral properties etc., however, these properties cannot be generalized to entire category of flavonoids, yet, may give an advantage over current anti-TNF agents [227,228].…”
Section: Natural Anti-tnf Agents: Focus On Flavonoidsmentioning
confidence: 99%
“…Terkait dengan penurun kolesterol, kuersetin dilaporkan memiliki efek kardioprotektif (Dower et al 2015), menurunkan risiko arterosklerosis (Sun et al 2015), dan meningkatkan efluks kolesterol pada liver serta meningkatkan perubahan kolesterol menjadi asam empedu (Zhang et al 2016). Berdasarkan laporan kemampuan kuersetin sebagai penurun kolesterol tersebut, kuersetin dapat digunakan sebagai senyawa penciri kualitas daun jati belanda sebagai penurun kolesterol.…”
Section: Hasil Dan Pembahasanunclassified